2022
DOI: 10.2174/1570159x19666210826142107
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehensive Neural Mechanism of Oxytocin in Analgesia

Abstract: : Oxytocin (OXT) is a nine amino acid neuropeptide hormone that has become one of the most intensively studied molecules in the past few decades. The vast majority of OXT is synthesized in the periventricular nucleus and supraoptic nucleus of the hypothalamus, and a few are synthesized in some peripheral organs (such as the uterus, ovaries, adrenal glands, thymus, pancreas, etc.) OXT modulates a series of physiological processes, including lactation, parturition, as well as some social behaviors. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…The immune regulatory and anti-inflammatory effects may have an impact on pain perception, although in humans there is evidence for altered oxytocin levels in some chronic pain conditions (Goodin et al, 2015;Mekhael et al, 2023). Importantly, oxytocin is now well established to act centrally, both in the spinal cord and brain, to reduce the perception of pain (Yang et al, 2022). These anti-nociceptive actions may be mediated by the oxytocin receptor itself or via interaction with opioid and other neuromodulator systems, but in addition the peptide has calming and anxiolytic effects (Kirsch et al, 2005;Neumann and Slattery, 2016;Herpertz et al, 2019), is often negatively correlated with cortisol, and can reduce stress (Lee et al, 2015;Schladt et al, 2017;Neumann and Landgraf, 2019).…”
Section: Oxytocinmentioning
confidence: 99%
See 2 more Smart Citations
“…The immune regulatory and anti-inflammatory effects may have an impact on pain perception, although in humans there is evidence for altered oxytocin levels in some chronic pain conditions (Goodin et al, 2015;Mekhael et al, 2023). Importantly, oxytocin is now well established to act centrally, both in the spinal cord and brain, to reduce the perception of pain (Yang et al, 2022). These anti-nociceptive actions may be mediated by the oxytocin receptor itself or via interaction with opioid and other neuromodulator systems, but in addition the peptide has calming and anxiolytic effects (Kirsch et al, 2005;Neumann and Slattery, 2016;Herpertz et al, 2019), is often negatively correlated with cortisol, and can reduce stress (Lee et al, 2015;Schladt et al, 2017;Neumann and Landgraf, 2019).…”
Section: Oxytocinmentioning
confidence: 99%
“…With regard to nociception, oxytocin influences physiological activity in known pain-related sites in the brain such as PAG, prefrontal and somatosensory cortex, ACC, insula, amygdala, NAc, raphe and hypothalamus (Figure 1) (e.g., Gu and Yu, 2007;Eliava et al, 2016;Boll et al, 2018;Poisbeau et al, 2018;Li et al, 2021;Saito et al, 2021;Nishimura et al, 2022;Yang et al, 2022;Iwasaki et al, 2023;Li et al, 2023a). Receptors are also found in the spinal cord and on a proportion of peripheral sensory neurons in the dorsal root ganglia (DRG) (Condes-Lara et al, 2005;Gong et al, 2015;González-Hernández et al, 2017;Poisbeau et al, 2018;Martinez-Lorenzana et al, 2021;Noguri et al, 2022;Yang et al, 2022;Li Y.-J. et al, 2023;.…”
Section: Oxytocinmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that OT can exert an anti-nociceptive action together with antiinflammatory and anxiolytic effects, thus improving perception and behavioral response to painful or aversive stimuli [74][75][76][77]. In particular, OT can exert its analgesic effect at both spinal cord level and above spinal cord level as well as in the peripheral nervous system.…”
Section: Role Of Oxytocin System In Attachment System and Pain Modula...mentioning
confidence: 99%
“…The amygdala, a limbic brain region, is essential in managing pain and affects the emotional and cognitive responses to it (11,12). Structural neuroimaging studies have demonstrated alterations in the volume of the amygdala in patients with CLBP, and these changes may be linked to their impaired cognitive-affective and emotional processing abilities, as well as to a more persistent chronic pain condition (6,13,14).…”
mentioning
confidence: 99%